The Physical Exercise as a Strategy of Reduce Costs with Medicine for Aged - Scolese, Marcela (Int J Prev Med, 2019)
BACKGROUND: To provide a critical reflection from the literature review to describe the current panorama on the importance of physical exercises in the improvement of the quality of life of the aged, besides the use of medications. While aging brings a high cost to health and demographic pyramid changes, so does the disease. As aging is a biological process and many diseases develop at this time of life, the aged are the fastest growing segment of the Brazilian population due to the natural susceptibility of the organism. With this increase, health costs in the country also increase. In everyday practice, medicine has often been characterized as a therapeutic intervention instrument for the first choice, and a consequence, generates significant and significant economic and social damages. METHODS: Search in databases using analysis descriptors as exercises and medicine for the aged. RESULTS: The involvement of the aged in physical exercise programs is an important adjunct to reduce the progressive degeneration associated with natural aging, becoming a powerful instrument to guarantee a healthy, active and independent lifestyle. CONCLUSIONS: The physical activity was inversely associated with the number of medications, the more physical activity and fewer drug expenses. The need to implement programs for orientation and for the promotion of health through physical activity was also verified.